Biomechanics of elite performers: Economy and efficiency of movement - Burns, G. T.; Kozloff, K. M.; Zernicke, R. F. (Kinesiology Review, 2019)
Movement is essential to the human experience, and efficient biomechanics facilitate effective action across the breadth of tasks one encounters in life. The concept of movement efficiency has been investigated and explored through a variety of means including biomechanical modeling, simulation, and experimental manipulation. Observations of elite performers for a given movement task serve as an additional line of insight into efficiency, as their movements have been driven toward optimization via competitive pressure. The authors first discuss the concept of efficiency in biomechanics from a qualitative perspective and the broad tools with which we explore it. They then highlight biomechanical investigations of elite performers and their contributions to our understanding of efficiency. Examples from various classes of movements illustrate unique insights of the elite performers in informing our understanding of movement efficiency.